2013
DOI: 10.1002/jgrd.50791
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization of Chinese daily surface air temperatures and analysis of trends in the extreme temperature indices

Abstract: [1] This study first homogenizes time series of daily maximum and minimum temperatures recorded at 825 stations in China over the period from 1951 to 2010, using both metadata and the penalized maximum t test with the first-order autocorrelation being accounted for to detect change points and using the quantile-matching algorithm to adjust the data time series to diminish discontinuities. Station relocation was found to be the main cause for discontinuities, followed by station automation. The effects of disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
153
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(163 citation statements)
references
References 68 publications
(97 reference statements)
4
153
0
Order By: Relevance
“…The SURF_CLI_CHN_MUL_DAY_V3.0 dataset contains data from 824 benchmark and basic weather stations across the country, providing high quality information on precipitation since January 1951. All data were compiled by the National Meteorological Information Center and subjected to a series of quality controls, including examining extreme values and an internal consistency check, and removal of questionable data according to the methods described by Xu et al [32]. The locations of the rain gauges are shown in Figure 1. …”
Section: Rain Gauge Datamentioning
confidence: 99%
“…The SURF_CLI_CHN_MUL_DAY_V3.0 dataset contains data from 824 benchmark and basic weather stations across the country, providing high quality information on precipitation since January 1951. All data were compiled by the National Meteorological Information Center and subjected to a series of quality controls, including examining extreme values and an internal consistency check, and removal of questionable data according to the methods described by Xu et al [32]. The locations of the rain gauges are shown in Figure 1. …”
Section: Rain Gauge Datamentioning
confidence: 99%
“…Homogenized daily temperatures at 2419 stations in China for the period 1951-2014 are available for this study (Xu et al 2013 …”
Section: S109mentioning
confidence: 99%
“…These studies found that it is more accurate and easier to analyze meteorological elements based on time series where significant breakpoints have been removed (Winkler Julie et al 1981;Alexandersson 1986). In recent years, homogenized historical temperature and precipitation observations in China have been developed by Chinese meteorologists; these represent a breakthrough in homogenization of surface observations (Li et al 2009Xu et al 2013), but homogenizing other meteorological elements remains an open question. The lack of data has restricted data assimilation, prediction, and forecasting for climate change; accordingly, it is important to increase the number of homogenization products available for current meteorological data processing.…”
Section: Introductionmentioning
confidence: 99%